Aluminum ion battery positive pole piece, aluminum ion battery and preparation method
By using 3,4-dioxyethylenethiophene: a mixture of polystyrene sulfonate and functional agent as the binder for the positive electrode sheet of an aluminum ion battery, the problems of poor conductivity and reaction with the electrolyte are solved, and a higher degree of performance has been achieved. The conductivity and stability of the aluminum ion battery improve the performance.
Patent Information
- Application Number
- CN202411509519.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The adhesive of existing aluminum ion batteries has poor electrical conductivity and is easy to react with the electrolyte, affecting battery performance.
A mixture of 3,4-dioxyethylenethiophene: a mixture of polystyrene sulfonate and functional agent is used as a new binder to form a crosslinking network through intermolecular hydrogen bonding to improve conductivity and adhesion.
The good conductivity, temperature resistance and adhesion of the positive electrode sheet of the aluminum ion battery are achieved, the dependence on conductive agents is reduced, the reaction with the electrolyte is avoided, and the cycle stability and overall performance of the battery are improved.
Smart Images

Figure CN119419272A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and more specifically, relates to an aluminum ion battery positive electrode sheet, an aluminum ion battery and a preparation method thereof. Background Art
[0002] Energy is the foundation for the survival and development of human society. However, with the advancement of science and technology, human demand for energy has increased significantly. Traditional fossil fuels have large carbon emissions, which will aggravate the greenhouse effect, cause serious damage to the environment, and are not conducive to sustainable development. Therefore, the development of new energy is of great significance to the adjustment of energy structure and is an inevitable requirement for achieving long-term sustainable development. Clean energy represented by solar energy and wind energy fluctuates greatly during the day and night and in different seasons, so it is crucial to develop energy storage technology to ensure the continuity of sustainable energy. The large-scale solar and wind energy storage market is huge, so the requirements for resources and costs are very high.
[0003] At present, lithium batteries with the best comprehensive performance occupy the main market. However, the existing lithium reserves are insufficient to meet the development needs of the energy storage industry. In addition, lithium-ion batteries also have safety and environmental pollution problems. Therefore, research on new energy storage technologies with low cost and abundant resources has become an important part of the development of grid-scale energy storage applications, and aluminum has the advantages of abundant reserves and low cost. The potential of aluminum-ion batteries for triple-charge energy storage makes them of high value in energy storage research. In addition, compared with lithium and sodium, aluminum has high safety. At present, the performance of aluminum-ion batteries is limited by factors such as the conductivity and mechanical strength of their electrode materials, and binders play a vital role in the preparation of electrode materials.
[0004] The positive electrode sheet is composed of active materials, binders and conductive agents. Traditional binders PVDF and PTFE have extremely poor conductivity. In aluminum-ion batteries, PVDF will react with traditional aluminum-ion battery electrolytes, so PTFE is used; however, the poor conductivity and adhesion of PTFE affect the overall performance of aluminum-ion batteries. Therefore, due to the poor conductivity of traditional binders and the problem that binders react with electrolytes, the performance of aluminum-ion positive electrode sheets is seriously affected, thereby affecting the performance of aluminum-ion batteries. Therefore, it is urgent to develop a new type of binder with water solubility and excellent conductivity. Summary of the invention
[0005] In view of the defects of the related art, the purpose of the present invention is to provide an aluminum ion battery positive electrode plate, an aluminum ion battery and a preparation method, aiming to solve the problem that the current traditional binders have poor conductivity and the binders react with the electrolyte, thereby reducing the performance of the aluminum ion battery.
[0006] To achieve the above-mentioned purpose, in the first aspect, the present invention provides an aluminum ion battery positive electrode plate, comprising: an active substance and a binder; the binder is a mixture of 3,4-dioxyethylenethiophene: polystyrene sulfonate and a functional agent; the active substance is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene; the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol and xylitol.
[0007] In a second aspect, the present invention further provides a method for preparing a positive electrode sheet for an aluminum ion battery, which is used to prepare the positive electrode sheet for an aluminum ion battery as described in the first aspect, comprising:
[0008] S1. Mix 3,4-dioxyethylenethiophene monomer and oxidant in deionized water according to a preset ratio and add polystyrene sulfonate to obtain 3,4-dioxyethylenethiophene:polystyrene sulfonate; the molar concentration ratio of 3,4-dioxyethylenethiophene monomer and oxidant in deionized water is 1:3-1:6; the oxidant is one of ferric chloride, potassium permanganate, potassium dichromate, hydrogen peroxide, and ammonium persulfate;
[0009] S2, washing 3,4-dioxythiophene:polystyrene sulfonate with acid and then drying it, and preparing an aqueous solution thereof;
[0010] S3, heating the aqueous solution and the functional agent to carry out a cross-linking reaction, and cooling to obtain a binder solution; the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol, and xylitol;
[0011] S4. Use a binder solution and an active material to make a positive electrode plate; the active material is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene.
[0012] Optionally, before S2, also include:
[0013] The 3,4-dioxyethylenethiophene:polystyrene sulfonate is dried to obtain powder.
[0014] Optionally, the acidic solution is one of concentrated sulfuric acid and concentrated nitric acid.
[0015] Optionally, the aqueous solution has a concentration of 1ω%.
[0016] Optionally, the total concentration of the aqueous solution and the functional agent is 15ω%.
[0017] In a third aspect, the present invention further provides an aluminum ion battery, comprising: a positive electrode sheet using the aluminum ion battery positive electrode sheet as described in the first aspect;
[0018] The negative electrode plate is aluminum foil, the electrolyte is aluminum ion battery electrolyte, and the current collector used in the battery cell is one of molybdenum foil, carbon cloth, and tantalum foil.
[0019] In a fourth aspect, the present invention further provides a method for preparing an aluminum ion battery, which is used to prepare the aluminum ion battery as described in the third aspect, comprising:
[0020] Assembling an aluminum ion battery cell containing the binder, wherein the positive electrode sheet is prepared according to the preparation method described in any one of the second aspects, and the negative electrode sheet is aluminum foil;
[0021] Adding aluminum ion battery electrolyte dropwise to the battery cell, encapsulating the cell in a glove box, and sealing the cell using a button cell structure to obtain an aluminum ion battery cell;
[0022] The aluminum ion battery is pre-shelved to allow the aluminum ion battery electrolyte to fully infiltrate the diaphragm in the aluminum ion battery cell to obtain an aluminum ion battery.
[0023] Compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects:
[0024] 1. The present invention provides a positive electrode plate for an aluminum ion battery. The positive electrode plate adopts a new type of binder, specifically a mixture of 3,4-dioxyethylenethiophene: polystyrene sulfonate and a functional agent. The binder has good electrical conductivity, so that the positive electrode plate can realize its function by only using active substances and binders, reducing or not requiring a conductive agent. The molecules of the binder form a strong cross-linked network through hydrogen bonds. The binder connects the active substances to each other through intermolecular forces (hydrogen bonds) to form conductive chains, and the conductive chains contact each other to form a larger conductive network, thereby playing the role of bonding and conductivity, and realizing that the positive electrode plate can realize its function without a conductive agent. The positive electrode plate using the binder has good electrical conductivity, temperature resistance and bonding properties, and the binder does not react with the electrolyte and does not affect the electrochemical performance of the battery, so that the battery cycle stability is better and the performance of the aluminum ion battery is improved.
[0025] 2. The present invention provides a method for preparing positive electrode sheets for aluminum ion batteries. In the process of preparing the positive electrode sheet slurry, better conductivity can be obtained without adding a conductive agent. The positive electrode sheet can be prepared with only active substances and the binder, which simplifies the slurry preparation process. During the preparation, the binder can be replaced by deionized water instead of the NMP solvent used in the preparation of traditional binders, responding to the call for environmental protection. Thereby, the process of preparing the positive electrode sheet is simplified, and the potential of the active substance is better exerted. Furthermore, TA (tannic acid) is used to further increase the adhesion while ensuring the water solubility and unchanged structure.
[0026] 3. The present invention provides an aluminum ion battery. The binder used in this solution has better conductivity and adhesion, and the binder does not react with the electrolyte to affect the electrochemical performance of the battery. The active substances in the battery can be fully utilized. The aluminum ion battery has better stability and improves the overall performance of the aluminum ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a charge and discharge curve of an aluminum ion battery provided by an embodiment of the present invention;
[0028] Figure 2 is a cycle curve of an aluminum ion battery provided by an embodiment of the present invention;
[0029] Figure 3 This is a cycle diagram of a graphite positive electrode aluminum battery in the prior art. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The contents involved in the above embodiment are described below in conjunction with a preferred embodiment.
[0032] Embodiment 1
[0033] The present invention provides an aluminum ion battery positive electrode sheet, comprising: an active material and a binder;
[0034] The binder is a mixture of 3,4-dioxyethylenethiophene:polystyrene sulfonate and a functional agent; the active substance is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene; and the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol and xylitol.
[0035] The binder is doped with 3,4-dioxyethylenethiophene PEDOT and polystyrene sulfonate PSS, and the anions of PSS form positive and negative electron pairs with the positive ions in the PEDOT molecules, so that the binder has conductivity; the functional agent is used to increase the bonding property of the binder;
[0036] The binder is used to connect the active materials to each other through intermolecular forces to form conductive chains, and the conductive chains contact each other to form a conductive network, which together constitute the positive electrode plate structure.
[0037] In traditional batteries, the positive electrode plate is usually composed of active materials, binders and conductive agents. However, in this scheme, a mixture of binders 3,4-dioxyethylenethiophene: polystyrene sulfonate (PEDOT: PSS) and tannic acid is used. Because the conjugated electron system between molecules of PEDOT itself has good connectivity and the ability of electron transmission within the molecular structure is strong, when doped with polystyrene sulfonate PSS, the anions of PSS form positive and negative electron pairs with the positive ions in the PEDOT molecules, so the binder has conductivity; in the positive electrode plate, the binder connects the active materials to each other through intermolecular forces (hydrogen bonds) to form conductive chains, and the conductive chains contact each other to form a larger conductive network, thereby playing the role of bonding and conduction. The binder has high conductivity and chemical stability, and does not need to add a conductive agent. The positive electrode plate composed of only active materials and binders can also achieve the original function; and, by reducing the conductive agent, the volume of the active material can be increased, thereby further increasing the conductive performance of the positive electrode plate.
[0038] In this scheme, the positive electrode sheet of the aluminum ion battery is prepared by the following method, including:
[0039] S1. Mix 3,4-dioxyethylenethiophene monomer and oxidant in deionized water according to a preset ratio and add polystyrene sulfonate to obtain 3,4-dioxyethylenethiophene:polystyrene sulfonate; the molar concentration ratio of 3,4-dioxyethylenethiophene monomer and oxidant in deionized water is 1:3-1:6; the oxidant is one of ferric chloride, potassium permanganate, potassium dichromate, hydrogen peroxide, and ammonium persulfate;
[0040] S2, washing 3,4-dioxythiophene:polystyrene sulfonate with acid and then drying it, and preparing an aqueous solution thereof;
[0041] S3, heating the aqueous solution and the functional agent to carry out a cross-linking reaction, and cooling to obtain a binder solution; the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol, and xylitol;
[0042] S4. Use a binder solution and an active material to make a positive electrode plate; the active material is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene.
[0043] In a specific embodiment, the oxidant is one of ferric chloride, potassium permanganate, potassium dichromate, hydrogen peroxide, and ammonium persulfate. For example, ferric chloride is selected. After selecting the oxidant, 3,4-dioxyethylenethiophene monomer (PEDOT) and the oxidant are mixed in deionized water to meet the molar concentration ratio of 1:3-1:6. The best molar concentration ratio is 1:4 through experiments. In this embodiment, the molar concentrations are set to 0.5 mol / L and 2 mol / L, respectively. Then, polystyrene sulfonate (PSS) with a mass ratio range of 1:1-1:6 is added thereto, and mechanical stirring is performed under an argon atmosphere to ensure that each component is evenly dispersed and reacts fully. Among them, polystyrene sulfonate has a better effect in this range. The more the dopant polystyrene sulfonate is added, the worse the conductivity of the binder will be.
[0044] After obtaining 3,4-dioxyethylenethiophene: polystyrene sulfonate (PEDOT:PSS), it is vacuum dried in an oven at 80°C for 24h to obtain a powder, and the powder is pickled in an acidic solution, and dried in a drying oven at 50°C-80°C to obtain a powder again, and an aqueous solution thereof is prepared, and the aqueous solution concentration is 1ω%. The acidic solution is one of concentrated sulfuric acid and concentrated nitric acid, and concentrated sulfuric acid is selected in this embodiment. Pickling with an acidic solution will open the shell-like PSS with poor conductivity wrapped outside the precursor structure of the binder, so that the binder has better conductivity.
[0045] After the configured aqueous solution and the functional agent are heated to 50°C-80°C, a cross-linking reaction is carried out, wherein the preferred temperature is 50°C to improve the stability and strength of the binder, and the binder solution is obtained after cooling. Wherein, the functional agent is one of tannic acid (TA), polyethylene oxide (PEO), sorbitol, polyethyleneimine, glycerol, and xylitol, and tannic acid is preferred in this embodiment. At the same time, the mass ratio of the aqueous solution to the functional agent is controlled to be 1:1, and the total concentration of the aqueous solution and the functional agent is 15ω%. Further, the binder solution and the active substance are prepared according to a preset mass ratio to form a positive electrode sheet, and the preset mass ratio range is 3:7-5:5. In this embodiment, the binder solution and the active substance are prepared according to a mass ratio of 3:7 to form a positive electrode sheet. Further, the active substance can be a conductive polymer, and in this embodiment, the active substance is preferably graphite.
[0046] The molecules of the binder obtained according to the above scheme form a strong cross-linked network through hydrogen bonds, so that it has excellent adhesion, chemical stability and conductivity, so that in the process of preparing the positive electrode slurry, better conductivity can be obtained without adding a conductive agent. The positive electrode can be prepared with only active substances and the binder, which simplifies the slurry preparation process.
[0047] In another specific embodiment, the oxidant is potassium permanganate, and the molar concentrations of 3,4-dioxyethylenethiophene monomer and potassium permanganate in deionized water are 0.5 mol / L and 2 mol / L, respectively. The mixture of 3,4-dioxyethylenethiophene monomer, potassium permanganate and polystyrene sulfonate is mechanically stirred under an argon atmosphere to ensure that each component is evenly dispersed and fully reacted. After obtaining 3,4-dioxyethylenethiophene: polystyrene sulfonate, it is vacuum dried in an oven at 80°C for 24 hours to obtain a powder, and the powder is pickled in concentrated nitric acid, and dried in a drying oven at 50°C-80°C to obtain a powder again, and its aqueous solution is prepared, and the concentration of the aqueous solution is 1ω%. The prepared aqueous solution and polyethylene oxide (functional agent) are heated to an appropriate temperature and then cross-linked to improve the stability and strength of the binder, and a binder solution is obtained after cooling. At the same time, the mass ratio of the aqueous solution to the functional agent is controlled to be 1:1.2, and the total concentration of the aqueous solution and the functional agent is 15ω%. Furthermore, the binder solution and the active material are mixed in a mass ratio of 4:6 to produce a positive electrode sheet, which has the same effect as the above embodiment and will not be described in detail.
[0048] In another specific embodiment, the oxidant is potassium dichromate, and the molar concentrations of 3,4-dioxythiophene monomer and potassium dichromate in deionized water are 0.5 mol / L and 2 mol / L, respectively. The mixture of 3,4-dioxythiophene monomer, potassium dichromate and polystyrene sulfonate is mechanically stirred under an argon atmosphere to ensure that each component is evenly dispersed and fully reacted. After obtaining 3,4-dioxythiophene: polystyrene sulfonate, it is vacuum dried in an oven at 80°C for 24 hours to obtain a powder, and the powder is pickled in concentrated nitric acid, and dried in a drying oven at 50°C-80°C to obtain a powder again, and its aqueous solution is prepared, and the concentration of the aqueous solution is 1ω%. The prepared aqueous solution and sorbitol (functional agent) are heated to an appropriate temperature and then cross-linked to improve the stability and strength of the binder, and the binder solution is obtained after cooling. At the same time, the mass ratio of the aqueous solution to the functional agent is controlled to be 1:1.5, and the total concentration of the aqueous solution and the functional agent is 15ω%. Furthermore, the binder solution and the active material are mixed in a mass ratio of 5:5 to prepare a positive electrode sheet, and the active material is polytriphenylamine. The effect is the same as that of the above embodiment, and will not be described in detail here.
[0049] Embodiment 2
[0050] On the basis of the above embodiment, after the positive electrode sheet is prepared, an aluminum ion battery using the positive electrode sheet can be manufactured. The positive electrode sheet in the aluminum ion battery adopts the positive electrode sheet of the aluminum ion battery described in the first embodiment; the negative electrode sheet is aluminum foil, the electrolyte is aluminum ion battery electrolyte, and the current collector used in the battery cell is one of molybdenum foil, carbon cloth, and tantalum foil.
[0051] The preparation of the aluminum ion battery specifically includes steps S1 to S4 in the above embodiment, and also includes:
[0052] S5. Assembling an aluminum ion battery cell containing the binder, wherein the positive electrode sheet is prepared according to the preparation method described in any one of the embodiments, and the negative electrode sheet is aluminum foil;
[0053] S6, adding aluminum ion battery electrolyte to the battery cell, packaging it in a glove box, and sealing it with a button battery structure to obtain an aluminum ion battery cell;
[0054] S7, pre-standing for a preset time to allow the aluminum ion battery electrolyte to fully infiltrate the diaphragm in the aluminum ion battery cell to obtain an aluminum ion battery.
[0055] In this embodiment, artificial graphite is selected as the active material; aluminum foil is selected as the negative electrode plate, and the current collector is selected from molybdenum foil, carbon cloth, and tantalum foil. When tantalum foil is selected as the current collector, it can have a better effect when used at a higher voltage; the electrolyte of the aluminum ion battery is 1-ethyl-3-methylimidazolium chloroaluminate chloride solution. The pre-standing time in S7 is 24 hours.
[0056] After the aluminum ion battery is prepared, its performance needs to be tested, so after S7, it also includes:
[0057] S8. The obtained aluminum ion battery is placed in a constant temperature box, and a constant current charge and discharge test is performed using a constant current charge and discharge instrument, and at the same time, the current, voltage, and capacity of the aluminum ion battery in the cycle are detected and collected in real time.
[0058] In the design of this example, the graphite positive electrode current collector is molybdenum foil, which is coated on one side and sliced on a slicer with a mold with a radius of 8mm to ensure that the active material load on each slice is about 0.8mg-1.2mg. After the battery is left for 24 hours to fully activate, the device is built. The actual aluminum ion battery containing the binder is placed in a constant temperature box, and the temperature of the constant temperature box is set to 45°C. In actual testing, the aluminum ion battery containing the binder needs to be fixed with a clamp, and the button battery is connected to a constant current charge and discharge instrument for subsequent data collection. The constant current charge and discharge mode is adopted, and the current density is 660mA g -1 The upper limit of the operating voltage is 2.5V, the lower limit is 0.05V, and the standby time during charging and discharging is 2min. During the test, the battery voltage, current, and capacity data are collected synchronously, and the collection time accuracy is not less than 1s, so as to facilitate subsequent analysis.
[0059] Subsequently, data analysis was performed on aluminum ion batteries containing the binder. Figure 1 and Figure 2 The electrochemical curve of the aluminum ion battery containing the binder in this example is shown. The battery operates well as a whole and its healthy life cycle reaches 2000 weeks. Figure 2 The second curve from top to bottom is the charge specific capacity, and the third curve is the discharge specific capacity. Figure 2The overcharge occurs because the anions in the electrolyte are embedded in the graphite material, which is a harmful side reaction. Figure 3 As shown, it represents the number of cycles of graphite positive electrode aluminum batteries. Compared with the existing technology, the aluminum ion battery of this scheme can be cycled more times while obtaining a higher charge and discharge specific capacity, and has a longer service life.
[0060] According to the aluminum ion battery prepared by the above preparation method, the binder used in the positive electrode sheet has good conductivity and high stability, and can reduce or even eliminate the use of conductive agents, thereby increasing the volume of active substances, exerting the potential of active substances, and improving the conductivity and chemical stability of aluminum ion batteries. Compared with the reaction between traditional PVDF and electrolyte, the binder of this scheme will not react with the electrolyte, and the aluminum ion battery will have a better cycle period; further, NMP used in traditional binders is a toxic organic solvent. When preparing aluminum ion batteries in this scheme, deionized water is used instead of NMP, which not only improves environmental performance but also reduces costs.
[0061] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A positive electrode sheet for an aluminum ion battery, characterized in that: include: Active material and binder; the binder is a mixture of 3,4-dioxyethylenethiophene:polystyrene sulfonate and a functional agent; the active material is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene; the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol and xylitol.
2. A method for preparing an aluminum ion battery positive electrode sheet, used to prepare the aluminum ion battery positive electrode sheet as claimed in claim 1, characterized in that: include: S1. Mix 3,4-dioxyethylenethiophene monomer and oxidant in deionized water according to a preset ratio and add polystyrene sulfonate to obtain 3,4-dioxyethylenethiophene:polystyrene sulfonate; the molar concentration ratio of 3,4-dioxyethylenethiophene monomer and oxidant in deionized water is 1:3-1:6; the oxidant is one of ferric chloride, potassium permanganate, potassium dichromate, hydrogen peroxide, and ammonium persulfate; S2, washing 3,4-dioxythiophene:polystyrene sulfonate with acid and then drying it, and preparing an aqueous solution thereof; S3, heating the aqueous solution and the functional agent to carry out a cross-linking reaction, and cooling to obtain a binder solution; the functional agent is one of tannic acid, polyethylene oxide, sorbitol, polyethyleneimine, glycerol, and xylitol; S4. Use a binder solution and an active material to make a positive electrode plate; the active material is one of graphite, polytriphenylamine, polydiphenylamine, polythiophene, polypyrrole, polyaniline and graphene.
3. The preparation method according to claim 2, characterized in that: Prior to S2, this also included: The 3,4-dioxyethylenethiophene:polystyrene sulfonate is dried to obtain powder.
4. The preparation method according to claim 3, characterized in that: The acidic solution is one of concentrated sulfuric acid and concentrated nitric acid.
5. The preparation method according to claim 2, characterized in that: The concentration of the aqueous solution is 1ω%.
6. The preparation method according to claim 5, characterized in that: The total concentration of the aqueous solution and the functional agent is 15ω%.
7. An aluminum ion battery, characterized in that: include: The positive electrode sheet adopts the positive electrode sheet of the aluminum ion battery as claimed in claim 1; The negative electrode plate is aluminum foil, the electrolyte is aluminum ion battery electrolyte, and the current collector used in the battery cell is one of molybdenum foil, carbon cloth, and tantalum foil.
8. A method for preparing an aluminum ion battery, for preparing the aluminum ion battery as claimed in claim 7, characterized in that: include: Assembling an aluminum ion battery cell containing the binder, wherein the positive electrode sheet is prepared according to the preparation method according to any one of claims 2 to 6, and the negative electrode sheet is aluminum foil; Adding aluminum ion battery electrolyte dropwise to the battery cell, encapsulating the cell in a glove box, and sealing the cell using a button cell structure to obtain an aluminum ion battery cell; The aluminum ion battery is pre-shelved to allow the aluminum ion battery electrolyte to fully infiltrate the diaphragm in the aluminum ion battery cell to obtain an aluminum ion battery.
Citation Information
Patent Citations
PEDOT: PSS / CMC composite binder and preparation method and application thereof
CN110890545A
Binder, battery and electric device
CN118406452A
Aluminum-ion battery assembly
US20200036033A1
Electroactive materials for secondary batteries
US20210320292A1
Aqueous binder of new chitosan and derivative thereof for lithium ion battery
WO2014008761A1
Cited By
Conductive-agent-free iodine positive electrode based on PEDOT: PSS and preparation method and application of conductive-agent-free iodine positive electrode
CN120854468A